2021
DOI: 10.1111/aogs.14091
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of fetal aneuploidy screening after the introduction of the non‐invasive prenatal test: A national population‐based register study

Abstract: IntroductionThe introduction of the non-invasive prenatal test (NIPT) has shifted the prenatal screening landscape. Countries are exploring ways to integrate NIPT in their national prenatal screening programs, either as a first-or second-tier test. This study aimed to describe how the uptake of fetal aneuploidy screening changed after the introduction of NIPT as a second-tier and as a first-tier test within the national prenatal screening program of the Netherlands. Material and methodsA population-based regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…In 2018, the uptake of fetal aneuploidy screening was 46% in the Netherlands, 8 whereas the uptake of the free‐of‐charge 20‐week fetal anomaly scan was 83% 27 . Moreover, Posthumus et al 10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2018, the uptake of fetal aneuploidy screening was 46% in the Netherlands, 8 whereas the uptake of the free‐of‐charge 20‐week fetal anomaly scan was 83% 27 . Moreover, Posthumus et al 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Advanced maternal age is an established risk‐factor for trisomy 21 34 . Previous research has shown that aneuploidy screening uptake is lower among women younger than 25, 8 likely due to a perceived lower risk of having a child with Down syndrome 35 . Because of this, the differences in uptake between socio‐economic disadvantaged and other areas may be less among younger women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The human rights of disabled people and their equality under the law are addressed by the Equality Act of 2010 (50), which followed the UK government's 2009 ratification of the UN Convention on the Rights of Persons with Disabilities (158). Termination of pregnancy on grounds of fetal anomaly is lawful within the terms of the 1967 Abortion Act in England, Scotland, and Wales (3).…”
Section: The United Kingdommentioning
confidence: 99%